Switching state vector selection for improved THD performance in multilevel current fed inverters - Reddy, G. Prem Kumar; Mangu, Bhukya (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This paper aims to explore synthesis methods of three-phase multi- level current waveforms by utilizing a configuration of n parallel operating three-phase, three-level current-fed inverters (CFIs). It points out an issue where differences in the DC-link current between inverters cause a distorted space vector diagram and decreased switching state redundancy, this leads to generation of low frequency harmonics in the output current and increased total harmonic distortion (THD). The research suggests a method that chooses the best switching state vectors by considering their closeness to a reference current space vector. This approach aims to decrease switching losses and low-frequency harmonic content. This method improves the quality of the waveform and the efficiency of the inverter by closely matching the switching operations with the intended current path. An analytical model is created to investigate how changes in DC-link current impact inverter performance. Simulations and actual tests confirm the ef-ficacy of the proposed strategy in enhancing total harmonic distortion (THD) and waveform accuracy. The results provide valuable information on improving multilevel inverter designs to enhance power quality and operational efficiency, indicating potential areas for further research in power electronics.